Overcoming Gadget Addiction Among Rural Adolescents through Traditional Games: A Case Study in Langkat Regency, North Sumatra - Kristina, Lina; Sampurna, Ahmad (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study examines solutions to address gadget addiction among children and adolescents in rural areas through traditional games characteristic of North Sumatra Province, such as Rimau Langkat, kite flying, stick fighting, and marbles. The research was conducted in Perlis Village, Berandan Barat District, Langkat Regency, North Sumatra Province. The research method used is qualitative, through participatory observation, interviews, and documentation study. The findings show that children and adolescents in the village have begun to be affected by gadget addiction, although not all of them are influenced by gadgets. The study in Perlis Village shows that they successfully overcame gadget addiction through traditional games, which managed to divert their attention from excessive gadget use. Traditional games like Rimau Langkat, kite flying, stick fighting, and marbles not only succeeded in reducing gadget dependence but also improved physical skills, social interaction, and a sense of togetherness among children. The phenomenon of gadget addiction, which initially led to decreased participation in social activities such as communal prayers and religious studies, now shows a positive change as children begin to interact directly and engage more actively in outdoor activities. This study refutes the argument that children and adolescents today are difficult to separate from gadgets, as they are considered part of their development and culture. This study concludes that children and adolescents can still be saved from the dangers of gadget addiction and that the local wisdom of rural communities can address the negative impacts of modernity, even though they do not reject it.